Attitudes and Perceptions of Tobacco-Related Products in College Students - Yen H. Dang (INNOVATIONS in Pharmacy, 2020)
Background – Despite the highly publicized health consequences, some college students do not perceive tobacco consumption as harmful. Historically-Black College and Universities (HBCUs) have the lowest rates of tobacco-free policies compared to other colleges, universities, and minority-serving institutions, making their students at higher risk for tobacco abuse. A campus Alcohol, Tobacco, and Other Drug Prevention Committee (ATDP) was formed and led by a pharmacist to develop all tobacco cessation policies at the HBCU.